Akuntabilitas Akuntan Perempuan-Karir Bali: Sebuah Studi Fenomenologi - Komalasari, Yeyen; Wirajaya, I Gde Ary; Ratna Sari, Maria Mediatrix (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
This study aims to understand how Balinese career women harmonize accountability practices. The study uses the interpretive paradigm and phenomenological approach to obtain a description of individual meaning and behavior comprehensively. The key informants in this study were women who were in the pragmatic endurance phase, i.e., the middle of their career in which they face a commitment to maintain a balance between their professional, community and personal or domestic life. The results showed that the multiple roles of Balinese career women were sourced from their self-owned accountability. Keywords:  Balinese career women, accountability practices, self-accountability